World Experience of Using Water Reservoirs in the Structure of Basic Horizontal Planes of an Architectural Object - Kuznietsova, Yana; ., . (International Journal of Engineering and Technology, 2018)
The aim of the article is to popularize the ecological approach in building both in Ukraine and states of the former Soviet Union. Previously the author studied issues of using water as a natural component on local and object levels in the structure of basic horizontal planes as connecting and outer spaces. This article deals with basic horizontal planes of buildings. The author analyzed architectural objects containing water as a natural component in their structure, and considered quality features of this approach. Firstly, these features influence psychology and physiology of a person, aesthetic perception of architectural objects and secondly, they have ecological aspects such as solving problems of heat isolation, precipitation cleansing, reducing the level of air pollution, atmospheric dispersion, etc. The article is based on the world experience of using water reservoirs in the structure of an architectural object. The author determined methods of water use and its influence on architectural form making. Watermorphic approach in architecture is defined as self-sufficient. Â Â